Corrective feedback in collaborative narrative writing for English as a second language learning in university students - Inostroza, Gabriel (2025)
According to the trends observed in the literature, studies related to corrective feedback are mostly quantitative and generally aim to compare the effectiveness of different ways of using it. The aim of this study was to explore the perceptions of student teachers of English regarding the delivery of written corrective feedback through the collaborative writing of narrative texts. The methodology applied corresponded to a qualitative research approach, using the phenomenology method by applying and analyzing semi-structured interviews with 12 first-year English teaching students from a Chilean university. These were conducted after a 5-session pedagogical intervention that included corrective feedback and collaborative writing strategies mediated by technological resources. The findings suggest that metalinguistic corrective feedback is necessary, since it helps to reinforce grammatical knowledge of English, and some participants also believe that its delivery should be regulated according to the level of knowledge or the number of instances of written activities. Therefore, based on these appreciations, the importance of exploring the types of feedback that students need according to the context in which they find themselves stands out.